2021
DOI: 10.1038/s41525-021-00200-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity index emerges as a potential biomarker for combined radiotherapy and immunotherapy

Abstract: In the era of immunotherapy, there lacks of a reliable genomic predictor to identify optimal patient populations in combined radiotherapy and immunotherapy (CRI). The purpose of this study is to investigate whether genomic scores defining radiosensitivity are associated with immune response. Genomic data from Merged Microarray-Acquired dataset (MMD) were established and the Cancer Genome Atlas (TCGA) were obtained. Based on rank-based regression model including 10 genes, radiosensitivity index (RSI) was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…However, this cutoff only classified 1.7% of brain glioma cases as RSI-low, whereas 98.3% were classified as RSI-high. Similarly, Dai et al [ 21 ] used the cutoff RSI value of 0.46 for stratification into RSI-low and RSI-high groups. A total of 8386 samples from the Merged Microarray-Acquired dataset (MMD) and a total of 6116 primary tumor samples from TCGA were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this cutoff only classified 1.7% of brain glioma cases as RSI-low, whereas 98.3% were classified as RSI-high. Similarly, Dai et al [ 21 ] used the cutoff RSI value of 0.46 for stratification into RSI-low and RSI-high groups. A total of 8386 samples from the Merged Microarray-Acquired dataset (MMD) and a total of 6116 primary tumor samples from TCGA were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The 12-chemokine signature was developed as a surrogate marker of immune activation for intratumoral lymphoid cell aggregates; however, the study population characterized by Strom et al did not include glioma patients. Dai et al [ 21 ] revealed that lower RSI scores were associated with higher proportions of M1 macrophages in two large transcriptome databases. These findings verify the relationship between radiosensitivity and immune status, particularly with respect to the proportions of M1 and M2 macrophages in the glioblastoma microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The broader utility remains a work in progress. [61][62][63] For many common cancers where RT is a crucial component of the first-line, curative-intent treatment, local failures (eg, in glioblastoma) or the lack of pathological complete response (eg, in rectal cancer) remain frustratingly common. 64 Our understanding of why the tumor is controlled in some patients but not in others remains limited.…”
Section: Clinical Research and Heterogeneity-based Treatmentmentioning
confidence: 99%